1986
DOI: 10.3109/03005368609079004
|View full text |Cite
|
Sign up to set email alerts
|

Speech levels and speech-to-noise ratios

Abstract: This investigation was concerned with the speech levels of both teachers and pupils in schools for the deaf and in units for partially-hearing children (PHUs) and with the levels of background noise found in these establishments. Twelve classes in 5 schools for the deaf and 8 PHUs were included in this study. The average speech level of the teachers, measured at 2 metres distance, was 57.5 dBA (range, 40-70 dBA) and that of the pupils was 52.9 dBA (range, 45-67 dBA). The levels of background noise measured wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 2 publications
1
21
0
1
Order By: Relevance
“…Furthermore, only students located close (proximal) to the teacher likely received the recommended SNR levels, while those at a distance (distal) never received the recommended levels, regardless of organizational setting. These findings are similar to SNRs measured in classrooms in prior studies (Finitzo-Hieber, 1988;Markides, 1986). Based on SNR standards and prior research, these results are disappointing, if not disturbing, and these settings should be viewed as hostile listening environments.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, only students located close (proximal) to the teacher likely received the recommended SNR levels, while those at a distance (distal) never received the recommended levels, regardless of organizational setting. These findings are similar to SNRs measured in classrooms in prior studies (Finitzo-Hieber, 1988;Markides, 1986). Based on SNR standards and prior research, these results are disappointing, if not disturbing, and these settings should be viewed as hostile listening environments.…”
Section: Discussionsupporting
confidence: 77%
“…Researchers have shown that poor acoustics and background noise make communication in classrooms dif cult (21,28,31). It is known that speakers unconsciously raise their voices in noisy conditions (the ''Lombard effect''); starting from 40 dB noise level there is 3 dB increase in speaking intensity (sound pressure level, SPL) for each 10 dB increase in noise (43).…”
Section: Teachers As a Group At Riskmentioning
confidence: 99%
“…Among professional voice users teachers form the largest group seeking medical help for their voice problems (10) and they are found to be at an exceptionally high risk of developing voice problems because of stress inherent in their occupation and the environmental conditions in which they work (9,15,21,25,27,28,37).…”
Section: Teachers As a Group At Riskmentioning
confidence: 99%
“…Picard and Bradley (2001) reviewed studies of noise levels in regular classrooms, and the mean level across studies for elementary schools was found to be 60 dBA, which is 10 dB greater than the average noise level reported for office spaces by Venetjoki et al (2006). SNRs in classrooms have been found to range between −6 and +3 dB (Blair, 1977; Crandell, 1993; Finitzo-Hieber, 1981; Markides, 1986), which are levels known to support word recognition scores of no greater than 60% correct for children (Nittrouer & Boothroyd, 1990; Nittrouer et al, 2011). Add to these challenging acoustic environments the fact that children’s goal in the classroom is to acquire new knowledge, which often involves new vocabulary, and it becomes clear that they could be hampered in their efforts to reach that goal.…”
mentioning
confidence: 99%